2015
DOI: 10.1093/mnras/stv1978
|View full text |Cite
|
Sign up to set email alerts
|

The Tully–Fisher and mass–size relations from halo abundance matching

Abstract: The Tully-Fisher relation (TFR) expresses the connection between rotating galaxies and the dark matter haloes they inhabit, and therefore contains a wealth of information about galaxy formation. We construct a general framework to investigate whether models based on halo abundance matching are able to reproduce the observed stellar mass TFR and mass-size relation (MSR), and use the data to constrain galaxy formation parameters. Our model tests a range of plausible scenarios, differing in the response of haloes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 107 publications
4
64
2
Order By: Relevance
“…However, Dutton et al (2007Dutton et al ( , 2011 showed that when models are constrained to reproduce the sizes of galaxies, they also overpredict the circular velocities if haloes contract in response to galaxy formation (Blumenthal et al 1986;Gnedin et al 2004). Such a conclusion has been verified by subsequent studies (e.g., Desmond & Wechsler 2015;Chan et al 2015).…”
Section: Introductionmentioning
confidence: 92%
“…However, Dutton et al (2007Dutton et al ( , 2011 showed that when models are constrained to reproduce the sizes of galaxies, they also overpredict the circular velocities if haloes contract in response to galaxy formation (Blumenthal et al 1986;Gnedin et al 2004). Such a conclusion has been verified by subsequent studies (e.g., Desmond & Wechsler 2015;Chan et al 2015).…”
Section: Introductionmentioning
confidence: 92%
“…However, both numerical hydrodynamic simulations (Faucher-Giguère et al 2011;Anglés-Alcázar et al 2016) and observations of galaxy gas content and consumption times at z ∼ 1-2 (Saintonge et al 2013;Genzel et al 2015) are inconsistent with gas accretion ceasing completely at z ∼ 1-2 in disk galaxies in Milky Way or smaller sized halos. Desmond & Wechsler (2015) investigated a model based on abundance matching and an angular momentum partition model similar to Eqn. 6, but allowing for expansion as well as contraction due to baryonic processes.…”
Section: Theoretical Expectations For Disk Sizesmentioning
confidence: 99%
“…Both of these quantities are expected to have significant halo-to-halo scatter. Indeed, Desmond & Wechsler (2015) showed that a model based on abundance matching plus an angular momentum partition type model similar to Eqn 6 produces too large a scatter in galaxy size at fixed stellar mass. Second, it holds across populations that are almost entirely disk dominated to ones that are almost entirely composed of giant ellipticals.…”
Section: Theoretical Expectations For Conditional Size Distributionsmentioning
confidence: 99%
“…Table 1. Comparison of statistics of the galaxy-halo connection in observations (P07), the EAGLE simulation, an abundance matching model with sizes chosen to match the stellar mass-size relation by construction ("SHAM"), and an analogous model with sizes set by angular momentum partition ("SHAM+MMW"; Desmond & Wechsler 2015). s MSR is the scatter in size of the stellar mass-size relation, ρ denotes Spearman rank correlation coefficient, and ∆ is defined in Eq.…”
Section: Data Models and Statisticsmentioning
confidence: 99%